2014
DOI: 10.1007/s10812-014-9955-0
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy in Cancer Diagnosis and Chemotherapy Monitoring

Abstract: We demonstrate that IR spectroscopic analysis can be used in diagnosis and chemotherapy monitoring for cancers of various organs at the molecular level. We used Fourier transform IR spectroscopy to study human breast and thyroid tumor tissues which were removed during surgery. The characteristic frequencies of C=O stretching vibrations in the IR spectra of tissues of pathological foci were compared with data from histological examination. In the IR spectra of healthy tissues or for benign tumors, the most inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is known that cancer progression is accompanied with biochemical modifications in cells, tissues, and body fluids before the appearance of alterations in cell morphology and body signs . Vibrational spectroscopy methods such as Fourier transform infrared spectroscopy (FTIR) can detect changes at a level of vibrations of molecular fragments and are a real perspective in this field of medicine .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cancer progression is accompanied with biochemical modifications in cells, tissues, and body fluids before the appearance of alterations in cell morphology and body signs . Vibrational spectroscopy methods such as Fourier transform infrared spectroscopy (FTIR) can detect changes at a level of vibrations of molecular fragments and are a real perspective in this field of medicine .…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy techniques are increasingly applied for progression modeling in different cancer subtypes due to their ability to create label-free molecular fingerprint definition of crucial biological molecules. Spectral features of treatment effectiveness can be assessed concerning clinical responsiveness as well as in comparison to healthy control using both supervised and unsupervised analytical methods [ 39 , 40 ]. Our previous studies reported a correlation between cancer tissue and FTIR spectral assessment [ 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tolstorozhev et al . have found that infrared spectroscopic analysis can be used in the diagnosis and treatment monitoring of cancers of various organs at the molecular level 22 . They found that when lung malignancy was treated with palladium complexes of methylenediphosphonic acid, the spectroscopic signs of the presence of metastases in the lungs disappear, and the infrared spectrum of the lung tissue after treatment practically coincides with the spectrum of healthy lung tissue.…”
Section: Discussionmentioning
confidence: 99%